The Evaluation of Innovative Susceptibility of Industrial Organizations of the Republic of Belarus - Y. V. Yemelyanchenko (Цифровая трансформация, 2019)
The article is devoted to the evaluation of innovative susceptibility of industrial organizations of the Republic of Belarus for 2014–2018. The author proposes a system of indicators of innovative susceptibility of industrial organizations, on the basis of which the assessment is carried out. It is established that Belarusian industrial organizations over the past five years have taken a number of measures to develop their innovative susceptibility, but there are problems that need to be addressed. The factors hindering innovations in the industrial organizations of the country are revealed. The work uses general scientific methods of cognition of economic phenomena and processes (analysis and synthesis, a systematic approach, the dialectical method, etc.). The significance of the work lies in the fact that such an assessment is currently absent in scientific research.